TANGGUNG JAWAB NOTARIS TERHADAP PENJAMIN FIDUSIA SEJAK DIBERLAKUKAN PENDAFTARAN FIDUSIA SECARA ELEKTRONIK - Rani Yusita (Repertorium: Jurnal Ilmiah Hukum Kenotariatan, 2016)
The Government has issued a circular from the Directorate General of AHU Kemenkumham year 06.OT.03.01 No. 20013 on the Electronic Registration Fiduciary guarantee, in the hope that the legal services in the field of fiduciary can run fast, accurate, free of extortion and able to encourage economic growth in Indonesia. Fiduciary registration with the electronic system makes it easier Fiduciary registration process, simply by filling the columns that have provided payment Fiduciary registration can be done at banks that have been determined, then the certificate can be directly printed fiduciary. The problem is how we lift the notary to the fiduciary responsibility in the event of errors in data entry while fiduciary certificates already issued electronically, and how the legal consequences of the creditors who registered late fiduciary electronically. This research is a normative law research, a document library research or studies conducted or directed only at the written regulations or other legal entity, whereas the data obtained through library research and field research. Furthermore, the data was analyzed qualitatively. The results showed that in the system of electronic registration of fiduciary Notary responsible for repairs fiduciary certificates, pay all costs incurred due to improved electronic data and registration certificate fiduciary guarantee on banks which have been designated / specified and print new sertikat. If the fiduciary is not registered it is not born fiduciary, the agreement is only an agreement accounts payable outstanding, so the status of the position of the creditor (recipient of fiduciary) only as a creditor konkruen. Thus, fiduciary recipient does not have the status of a creditor precedence (preference) that the creditor has the right decision prior repayment rights of the other creditors. Also according to the provisions of Article 5 of Regulation meteri Finance (PMK RI) No. 130 / PMK / 010/2012 that the finance company does not mendaftrakan fiduciary will be witness to an administrative form of warnings, suspension of business activity and revocation of business licenses. Keywords: Fiduciary Electronics, Responsibility, Notary.